Increasing serum Pre-adipocyte factor-1 (Pref-1) correlates with decreased body fat, increased free fatty acids, and level of recent alcohol consumption in excessive alcohol drinkers - Liangpunsakul, Suthat (Alcohol, 2014)
BACKGROUND: Patients with alcoholic liver disease have been reported to have a significantly lower percentage of body fat (%BF) than controls. The mechanism for the reduction in %BF in heavy alcohol users has not been elucidated. In adipose tissue, Pref-1 is specifically expressed in pre-adipocytes but not in adipocytes. Pref-1 inhibits adipogenesis and elevated levels are associated with reduced adipose tissue mass. We investigated the association between serum Pref-1 and %BF, alcohol consumption, and serum free fatty acids (FFA) in a well-characterized cohort of heavy alcohol users compared to controls. METHODS: One hundred forty-eight subjects were prospectively recruited. The Time Line Follow-Back (TLFB) questionnaire was used to quantify the amount of alcohol consumed over the 30-day period before their enrollment. Anthropometric measurements were performed to calculate %BF. Serum Pref-1 and FFA were measured. RESULTS: Fifty-one subjects (mean age 32 ± 9 years, 88% men) were non-excessive drinkers whereas 97 were excessive drinkers (mean age 41 ± 18 years, 69% men). Compared to non-excessive drinkers, individuals with excessive drinking had significantly higher levels of Pref-1 (p < 0.01), FFA (p < 0.001), and lower %BF (p = 0.03). Serum levels of Pref-1 were associated with the amount of alcohol consumed during the previous 30 days. Serum Pref-1 was negatively correlated with %BF, but positively associated with serum FFA. CONCLUSIONS: Our data suggest that elevated Pref-1 levels in excessive drinkers might inhibit the expansion of adipose tissue, decreasing %BF in alcoholics. Further work is needed to validate these findings and to better understand the role of Pref-1 and its clinical significance in subjects with heavy alcohol use.